Noctiluca Scintillans Distribution Largely Regulated by Phytoplankton Biomass in the East China Sea and Southern Yellow Sea - Sheng, Liuyang; Jiang, Zhibing; Sun, Zhenhao; Zhu, Yuanli; Zhai, Hongchang; Ding, Ling; Tong, Mengmeng; Chen, Jianfang; Chen, Quanzhen; Zeng, Jiangning (Frontiers in Marine Science, 2022)
Noctiluca scintillans feeds on a large number of phytoplankton, including diatoms and dinoflagellates, and frequently forms a red tide in the East China Sea (ECS) and southern Yellow Sea (SYS). However, the spatiotemporal distribution pattern, controlling factors, and long-term change of N. scintillans in the ECS and SYS remain unclear. In the present study, we collected N. scintillans samples from the ECS and SYS throughout the four seasons of 2011. We sampled phytoplankton and environmental parameters simultaneously. The depth-integrated abundance (DIA) of N. scintillans was the highest and lowest in summer and winter, respectively. N. scintillans is distributed abundantly in eutrophic coastal waters and the Changjiang Estuary, which are characterized by high concentrations of phytoplankton and chlorophyll-a. A Spearman correlation test demonstrated that its DIA in the upper 30-m water column was generally more significantly associated with phytoplankton abundance and chlorophyll-a concentration than with temperature and salinity. The results of the generalized additive models revealed that chlorophyll-a concentration explained more of the variation in N. scintillans abundance than temperature and salinity throughout the year, particularly in warm seasons. These findings indicate that the seasonal and spatial changes of N. scintillans are largely regulated by phytoplankton biomass. Compared with the historical data from 1959 and 2002, the abundance of N. scintillans in the Changjiang Estuary increased considerably in 2011 with increasing phytoplankton abundance resulting from accelerated eutrophication and warming. These results clarify the controlling factors, red-tide formation mechanism, and changing trends associated with the N. scintillans in the ECS and SYS.